Pusat Pendidikan Dan Terapi Anak Autis Di SukoharjoDengan Pendekatan Behaviour Architecture - Sani, Kinan Kartika; , Dr. Ir. Dhani Mutiari, MT (2016)
ABSTRACT Education and Therapy Center in Sukoharjo Autistic Children with Behaviour Architecture Approach is an educational center that cater for children with autism to create an atmosphere of interactive space in an atmosphere of learning and therapeutic atmosphere. In addition, Education and Therapy Center's facilities include a sensory garden for children with autism to train motor disorders suffered by them. Besides, the Centre for Education and Autism Therapy facilities to develop the talents of children, such as skills classes, music classes and dance classes. Education and Therapy Center is expected to become an information center for people with autism in Sukoharjo district. Behaviour Architecture approach used as the basis for designing buildings that are tailored to the behavior of autistic children by not forgetting the aspect of comfort and safety. This is because the behavior of children with autism is different from other normal child behavior. By adjusting the behavior of children with autism are expected to support the learning process and the therapeutic process them into a more positive direction. So that the child can give a good response to the surrounding environment in the community. Keywords: autism, behaviour architecture, interaktif, sensory garden, therapy